1966
DOI: 10.1002/cne.901260103
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal changes in epidermal innervation in rat and mouse

Abstract: The development of cutaneous innervation in the rat and the mouse has been studied by silver techniques. In particular, the innervation patterns of adult and of perinatal skin have been compared. From the second prenatal day until the sixth postnatal day, the relatively thick epidermis is freely penetrated by nerve fibers; thereafter, the nerve endings appear to be confined to the dermis. The intraepidermal axans are directed obliquely, with a rough (and not exact) correspondence to the plane of future emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…have affected neuronal transport in two ways: nerve section, which totally interrupts all transport as well as impulse conduction, and colchicine application which, as measured by its effect on cholinesterase and catecholamine flow, partially interrupts fast axoplasmic transport, but does not affect impulse conduction (Aguilar et al 1973;M. Holmes, C. Turner, J. A Fried, E. Cooper and J.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have affected neuronal transport in two ways: nerve section, which totally interrupts all transport as well as impulse conduction, and colchicine application which, as measured by its effect on cholinesterase and catecholamine flow, partially interrupts fast axoplasmic transport, but does not affect impulse conduction (Aguilar et al 1973;M. Holmes, C. Turner, J. A Fried, E. Cooper and J.…”
Section: Resultsmentioning
confidence: 99%
“…Ramon y Cajal (1919) pointed out that sprouting of nerves during primary development occurs only when the nerves arrive at their targettissues, in the case of epithelium at least; his suggestion to explain this phenomenon is analogous to our hypothesis, namely that a sprouting stimulus derives from the target-tissue, and becomes eventually neutralized by factors released from the nerve. The findings of Fitzgerald (1961) on the development of the innervation of the pig snout suggest that a targettissue can be matched throughout its growth by an appropriate increase in the nerve endings without a change in the number of parent axons; the density of innervation stays constant. More target-tissue would presumably make more sprouting stimulus, so inducing sprouting until the equilibrium state is reached.…”
Section: Other Examples Of Collateral Sproutingmentioning
confidence: 99%
“…Axons reach trunk skin by El3 but do not reach the most distal skin in the toes until as late as E 19 (Reynolds et al,199 1). Sensory axons do not immediately innervate targets in the skin but form a dense plexus in the epidermis that persists for the next several days (Fitzgerald, 1967;Reynolds et al, 1991). Most of these fibers then withdraw from the epidermis between PND 5 and 10 to innervate structures such as hair follicles in the dermis, with withdrawal of more rostra1 innervation occurring in advance of that of more caudal innervation.…”
Section: Discussionmentioning
confidence: 99%
“…Arthur and Shelley (1959) and Fitzgerald (1961) suggested that free nerve endings that extend into the epidermis (Sect. 1.2.4) serve as sensory afferents.…”
Section: Suggested Biological Relevance Of Electrodermal Phenomenamentioning
confidence: 99%